"I enjoy thinking critically, and I'm in control": Examining the influences of media literacy factors on misperceptions amidst the COVID-19 infodemic. (March 2022) - Su, Yan; Lee, Danielle Ka Lai; Xiao, Xizhu
Abstract: Misinformation circulation has arguably reached a peak during the COVID-19 pandemic, creating an "infodemic" that severely endangers public health and well-being. Using a moderated mediation model, a survey of 712 respondents from China reveals that social media information seeking is positively associated with COVID-19 misperceptions, while need for cognition (NFC) is negatively associated with it. Both relationships became more significant while mediating through individuals' general misperceptions. Moreover, it is found that among those with greater locus of control over media, the association between social media information seeking and COVID-19 misperceptions became more positive, while the association between NFC and COVID-19 misperceptions became more negative among those with greater media locus of control. Findings provide insights into the misperception research and have practical implications regarding infodemic management. Highlights: Social media information-seeking is positively associated with COVID-19 misperceptions. Need for cognition is negatively associated with COVID-19 related misperceptions. General misperceptions serve as a significant mediator. Media locus of control is a significant moderator.